Research on the Construction of Digital Teaching Resources for Schools Oriented to Teaching Innovation - Zhao Zixuan (SHS Web of Conferences, 2023)
With the continuous further development of education informatization in our country, the present way and the way of spreading knowledge have changed gradually, which has caused innovation of teaching mode, teaching method and learning method. In the information teaching environment, as an important resource in the implementation of the teaching process, digital teaching resources have become the focus of basic education schools gradually. Schools have begun to explore the construction of digital high-quality teaching resources with their own characteristics, so as to promote the teaching reform and innovation of schools. In order to explore the effective measures and effects of the construction of digital teaching resources in combination with the needs of teaching innovation, this study carried out various comprehensive studies. This paper first introduces the dimension and principle of teaching innovation to provide theoretical basis for the research. Secondly, this paper puts forward the countermeasures to promote the construction of digital teaching resources in schools, to provide reference for related research.